Airborne Observations of Summer Thinning of Multiyear Sea Ice Originating From the Lincoln Sea. Issue 1 (14th January 2019) - Lange, Benjamin A.; Beckers, Justin F.; Casey, J. Alec; Haas, Christian
Abstract: To better understand recent changes of Arctic sea ice thickness and extent, it is important to distinguish between the contributions of winter growth and summer melt to the sea ice mass balance. In this study we present a Lagrangian approach to quantify summer sea ice melt in which multiyear ice (MYI) floes that were surveyed by airborne electromagnetic thickness sounding within Nares Strait during summer were backtracked, using satellite imagery, to a region in close proximity (3–20 km) to spring ice thickness surveys carried out in the Lincoln Sea. Typical modal total MYI thicknesses, including 0.4‐m snow, ranged between 3.9 and 4.7 m in the Lincoln Sea during April. Ice‐only modal thicknesses were between 2.2 and 3.0 m in Nares Strait during August. Total thinning including snow and ice was 1.3 ± 0.1 m including 0.4 ± 0.09 m of snow melt and 0.9 ± 0.2 m of ice melt. This translates to a seasonal net heat input of 305 ± 69 MJ/m 2 (262 ± 60 MJ/m 2 for ice only) and seasonal net heat flux of 57 ± 13 W/m 2 (45 ± 10 W/m 2 for ice only), which is unlikely to be explained by solar radiation fluxes alone. Furthermore, our approach provides an improvement on traditional ice mass balance buoy estimates because it integrates melt over larger spatial scales, where melt can be highly variable due to differential melt experienced between melt ponds, bare ice, hummocks, and ridges. Plain Language Summary: Some of the oldest and thickest sea ice remains in a small region between Canada, Greenland and the North Pole, the so‐called "Last Ice Area", and will retain this ice longest into the future. Thus, continued monitoring of this unique sea ice habitat is crucial in order to document ongoing changes in the physical environment and to better predict the fate of many animals that depend on sea ice for survival (e.g., polar bears and seals). In this study, we compared sea ice thickness measurements from spring and summer to provide a better understanding of how the ice changes from season to season. Ice thickness changes provide important information on the Arctic Ocean's energy budget, a good indicator of the health of the Arctic Ocean. Our measurements are particularly important because they are the first of their kind over old, thick ice during summer in this unique region. We showed that 0.9 m of old sea ice melted from spring to summer. Although this is comparable to previous studies of old ice, it is important to continue these measurements in order document the expected ongoing changes to the sea ice environment and monitor the health of the Arctic Ocean. Key Points: MYI surveyed in the Lincoln Sea during spring had modal thicknesses of 3.9‐4.7 m, which thinned to 2.2‐3.0 m in summer in Nares Strait Backtracking individual floes with satellite images was used to reconstruct positions of the same ice fields surveyed in spring and summer Estimated sea ice melt was 0.9 +/‐ 0.2 m, slightly higher than observations by ice mass balance buoys for the same region